Success rates of simulated multi-pulse defibrillation protocols are sensitive to application timing with individual, protocol-specific optimal timings - Aron, Marcel; Luther, Stefan; Parlitz, Ulrich (Frontiers in Network Physiology, 2025)
Ventricular fibrillation is a lethal condition where the heartbeat becomes too disorganised to maintain proper circulation. It is treated with defibrillation, which applies an electric shock in an attempt to reset the heart rhythm. As the high energy of this shock risks long-term harm to the patient, means of reducing it without compromising treatment efficacy are of great interest. One approach to maintaining efficacy is to improve the success rate of such low-energy shocks (i.e., pulses) through the proper timing of their application as defibrillation protocols, which consist of one or more pulses with predetermined inter-pulse periods. In practice, however, the effects of application timing remain to be tested for any of the multi-pulse protocols proposed in literature. We use (de)fibrillation simulations to show that such timing matters: The success rate of single-pulse protocols can vary by as much as 80 percentage points depending on timing, and using more shocks in succession only lessens this sensitivity up to a point. We also present evidence that feedback-based defibrillation on a shock-by-shock basis may be the only practical means of using timing to increase treatment efficacy, as we also generally find any optimal application timings to be specific to each combination of protocol and fibrillation episode.